2021
DOI: 10.1159/000520444
|View full text |Cite
|
Sign up to set email alerts
|

Salidroside Attenuates Airway Inflammation and Remodeling via the miR-323-3p/SOCS5 Axis in Asthmatic Mice

Abstract: <b><i>Introduction:</i></b> Salidroside (Sal) a bioactive component extracted from <i>Rhodiola rosea</i> is remarkable for its anti-asthmatic effects. The study aimed to explore the molecular mechanism of Sal in airway inflammation and remodeling in asthmatic mice and provide a novel theoretical basis for asthma treatment. <b><i>Methods:</i></b> An asthmatic mouse model was established via ovalbumin (OVA) treatment, followed by injection of Sal and tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“… 39 Furthermore, salidroside has been shown to alleviate airway inflammation and remodeling in asthmatic mice by suppressing the expression of the miR-323-3p in the cytokine signaling 5 (SOCS5). 40 In this study, we showed that salidroside inhibited miRNA-199a-5p, increased the TNFAIP8L2, decreased the HMGB1/TLR4/NF-κB signaling pathway, decreased the secretion of inflammatory cytokine molecules in the MLE-12 cells, and assuaged the endotoxin-induced acute lung injuries.…”
Section: Discussionmentioning
confidence: 65%
“… 39 Furthermore, salidroside has been shown to alleviate airway inflammation and remodeling in asthmatic mice by suppressing the expression of the miR-323-3p in the cytokine signaling 5 (SOCS5). 40 In this study, we showed that salidroside inhibited miRNA-199a-5p, increased the TNFAIP8L2, decreased the HMGB1/TLR4/NF-κB signaling pathway, decreased the secretion of inflammatory cytokine molecules in the MLE-12 cells, and assuaged the endotoxin-induced acute lung injuries.…”
Section: Discussionmentioning
confidence: 65%
“…Salidroside, which is extracted from the root of Rhodiola rosea L, plays a critical role in multiple processes, like anti‐oxidation, anti‐aging, cancer‐related therapy, and especially in anti‐inflammation (Fan, Su, et al, 2022; Fan, Xu, et al, 2022; Jin et al, 2016; Ma et al, 2021; Wang et al, 2022). Researchers found that salidroside could ameliorate ovalbumin‐induced airway inflammation and hyperresponsiveness in asthma mice and inhibit the microglial inflammation induced by hypoxia (Fan, Su, et al, 2022; Fan, Xu, et al, 2022; Luan et al, 2022; Ming et al, 2022). Besides, it was also reported that salidroside could alleviate furan‐induced liver inflammation and improve the P4HB‐mediated inflammation of skin (Ding et al, 2020; Yuan et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…SOCS family proteins are a class of negative regulators of JAK2-STAT3 signaling pathway, consisting of SOCS1-7, both containing Src-homology domian and a conserved C-termial domain [ 46 ]. Among them, SOCS5 is expressed in a variety of adult tissues, playing anti-inflammatory, anti-tumor, anti-oxidative stress and other functions [ 16 , 47 , 48 ]. Xi et al uncovered that salidroside could promote SOCS5 transcription to reduce airway inflammation and airway remodeling in asthmatic mice [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among them, SOCS5 is expressed in a variety of adult tissues, playing anti-inflammatory, anti-tumor, anti-oxidative stress and other functions [ 16 , 47 , 48 ]. Xi et al uncovered that salidroside could promote SOCS5 transcription to reduce airway inflammation and airway remodeling in asthmatic mice [ 48 ]. Tsai et al also proved that SOCS5 was highly expressed in high glucose-induced renal mesangial cells, which led to the inactivation of JAK2/STAT3 pathway [ 49 ].…”
Section: Discussionmentioning
confidence: 99%